Awareness of LASER in periodontal therapy among periodontal practitioners in Chennai: A questionnaire survey - Paavai Ilango; G D Gomathi; Abirami Thanigaimalai; Ayswarya V Vummidi; Arulpari Mahalingam; Vineela Katam Reddy (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the study was to analyze the awareness of LASER in periodontal treatment modalities and their advantages and disadvantages among periodontists in Chennai, India. Materials and Methods: Seventy periodontists, including postgraduate students, were evaluated on their awareness on LASER using a validated questionnaire. The answers were recorded, and scoring was given based on their choices. The scores were statistically evaluated. Results: The results suggested a profound awareness of LASER (55.7% had more than 3 years of experience and 44.3% had <3 years of experience) toward application for periodontal therapy. Nearly 18.6% of periodontists felt that LASER is a replacement for scalpel, whereas 34.3% felt LASER cannot completely replace scalpel and 47.1% of them felt it debatable. About 34.3% reported LASER as an adjunct, 18.7% reported it to be a standalone surgical tool, and 47.1% of them felt it debatable. Conclusion: This study implies that most of the periodontists have profound knowledge on the basic concepts of LASER and its application in periodontal treatment. The study also infers the use of LASER has become more predominant among periodontists in their day-to-day practice.